Synthesis and biological profile of 2,3-dihydro[1,3]thiazolo[4,5-b]pyridines, a novel class of acyl-ACP thioesterase inhibitors - Frackenpohl, Jens; Barber, David M.; Bojack, Guido; Bollenbach-Wahl, Birgit; Braun, Ralf; Getachew, Rahel; Hohmann, Sabine; Ko, Kwang-Yoon; Kurowski, Karoline; Laber, Bernd; Mattison, Rebecca L.; Müller, Thomas; et al. (Beilstein Journal of Organic Chemistry, 2024)
The present work covers novel herbicidal lead structures that contain a 2,3-dihydro[1,3]thiazolo[4,5-b]pyridine scaffold as structural key feature carrying a substituted phenyl side chain. These new compounds show good acyl-ACP thioesterase inhibition in line with strong herbicidal activity against commercially important weeds in broadacre crops, e.g., wheat and corn. The desired substituted 2,3-dihydro[1,3]thiazolo[4,5-b]pyridines were prepared via an optimized BH3-mediated reduction involving tris(pentafluorophenyl)borane as a strong Lewis acid. Remarkably, greenhouse trials showed that some of the target compounds outlined herein display promising control of grass weed species in preemergence application, combined with a dose response window that enables partial selectivity in certain crops.
Keywords: 2,3-dihydro[1,3]thiazolo[4,5-b]pyridine; acyl-ACP thioesterase; bioisostere; herbicide; heterocycle